ICD-10-CM extension with ICD-9 diagnosis codes to support integrated access to clinical legacy data. (September 2019) - Hernandez-Ibarburu, G.; Perez-Rey, D.; Alonso-Oset, E.; Alonso-Calvo, R.; de Schepper, K.; Meloni, L.; Claerhout, B.
Highlights: Methodology for the integration of ICD-9 diagnosis legacy data with ICD-10-CM data. Extension of ICD-10-CM with ICD-9 diagnosis concepts. Identification of incompatibilities between ICD-9 and ICD-10-CM. Mapping rules from ICD-9 to ICD-10-CM to increase the mapping reliability. Abstract: Introduction: ICD is currently the most widely used terminology to code diagnosis and procedures. The transition from ICD-9-CM to ICD-10-CM became effective on October 1, 2015 in US and many other countries. Projects that use this codification for research purposes, requires advanced methods to exploit data with both versions of ICD. Although the General Equivalence Mappings (GEMs), provided by the Centers for Medicare and Medicaid Services, might help to overcome these challenges, their direct use as translation mappings is not possible, mostly due to the further specificity of ICD-10-CM concepts. Objective: We propose a methodology to generate an extended version of ICD-10-CM with selected ICD-9-CM diagnosis codes. Methods: The extension was generated using the GEMs relations between concepts of both terminologies and the hierarchical relations of ICD-10-CM. Results: This extended ICD-10-CM, together with modifications to the mapping of ICD-9-CM concepts that were not inserted, allows the generation of an improved translation of legacy data, raising the number of 1-to-1 correspondences by +13.81%. Conclusion: The extended ICD-10-CM enables the accurate integration of ICD-9-CM and ICD-10-CM diagnosis data into a single terminology. With such analysis of data possible without having to specify both ICD-9-CM and ICD-10-CM separately for each query.